Factors influencing the decision-making of carers of children with bilateral cataract in Nepal. Issue 1 (6th April 2020) - Bell, Suzannah J; Singh, Tirtha; Bunce, Catey; Singh, Sanjay Kumar; Bascaran, Cova; Gilbert, Clare; Foster, Allen
Abstract : Objectives: Two hundred thousand children worldwide are blind from cataract. Late presentation for surgery resulting in poor visual outcomes is a problem globally. We aimed to explore the reasons why children are not brought earlier for surgery in Nepal. Methods and analysis: Mixed-method study of carers of children with bilateral cataract attending a large non-government eye hospital were administered a proforma. A random sample took part in semistructured interviews and focus group discussions. Results: Carers of 102 children completed proformas; 10 interviews and 2 focus group discussions were held. 80.4% were Indian, 35.3% of children were female, and their mean age was 58 months (range 4 months to 10 years). Median delay in time between the carer first noticing a problem to presentation was 182 days IQR (60.8–364.8). This was significantly longer for girls (median 304 IQR (91.2–1094.4)) than boys (median 121.6 IQR (30.4–364.8); p=0.02). Cost to access care was a problem for 42 (41.2%) carers. 13 (12.8%) participants were not aware of treatment and 12 (11.8%) were aware but did not seek treatment. The community influenced carer's health-seeking behaviour. Cataract was sometimes described as 'phula', meaning something white seen on the eye. Conclusion: Fewer girls presented for surgery, and they also had a significantly longer delay to presentation than boys. Carers are influenced by factors at family, community and socio-organisational levels. Approaches to increase timely access, particularly by girls, are required, such as health education using the term phula, which is widely understood.